2011
DOI: 10.1107/s1600536811028054
|View full text |Cite
|
Sign up to set email alerts
|

[2,7-Dimethoxy-8-(2-naphthoyl)naphthalen-1-yl](naphthalen-2-yl)methanone

Abstract: The mol­ecule of the title compound, C34H24O4, possesses crystallographically imposed twofold C 2 symmetry. The two 2-naphthoyl groups at the 1- and 8-positions of the central naphthalene ring are aligned almost anti­parallel [5.21 (5)°]. The dihedral angle between the central 2,7-dimeth­oxy­naphthalene unit and the terminal naphthyl groups is 75.13 (4)°. In the crystal, weak C—H⋯O hydrogen bonds and π–π stacking inter­actions [centroid–centroid and inter­planar distances are 3.6486 (8) and 3.3734 (5) Å, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recently, the authors have found highly efficient diaroylation at peri (1,8)-positions of 2,7-dialkoxynaphthalene compounds [5,6]. peri-Aroylated naphthalene compounds thus obtained are proved to have non-coplanarly accumulated aromatic-rings-structure in crystal, i.e., the aroyl groups are twistedly situated to the naphthalene ring core in a perpendicular fashion [7][8][9]. Besides, the two aroyl groups are ordinarily oriented in an opposite direction with a few exceptional compounds bearing unidirectionally-aligned aroyl groups [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors have found highly efficient diaroylation at peri (1,8)-positions of 2,7-dialkoxynaphthalene compounds [5,6]. peri-Aroylated naphthalene compounds thus obtained are proved to have non-coplanarly accumulated aromatic-rings-structure in crystal, i.e., the aroyl groups are twistedly situated to the naphthalene ring core in a perpendicular fashion [7][8][9]. Besides, the two aroyl groups are ordinarily oriented in an opposite direction with a few exceptional compounds bearing unidirectionally-aligned aroyl groups [10,11].…”
Section: Introductionmentioning
confidence: 99%